The mutagenesis protein UmuC is a DNA polymerase activated by UmuD', RecA, and SSB and is specialized for translesion replication - Reuven, N B; Arad, G; Maor-Shoshani, A; Livneh, Z (The Journal of biological chemistry, 1999)
Replication of DNA lesions leads to the formation of mutations. In Escherichia coli this process is regulated by the SOS stress response, and requires the mutagenesis proteins UmuC and UmuD'. Analysis of translesion replication using a recently reconstituted in vitro system (Reuven, N. B., Tomer, G., and Livneh, Z. (1998) Mol. Cell 2, 191-199) revealed that lesion bypass occurred with a UmuC fusion protein, UmuD', RecA, and SSB in the absence of added DNA polymerase. Further analysis revealed that UmuC was a DNA polymerase (E. coli DNA polymerase V), with a weak polymerizing activity. Upon addition of UmuD', RecA, and SSB, the UmuC DNA polymerase was greatly activated, and replicated a synthetic abasic site with great efficiency (45% bypass in 6 min), 10-100-fold higher than E. coli DNA polymerases I, II, or III holoenzyme. Analysis of bypass products revealed insertion of primarily dAMP (69%), and to a lesser degree dGMP (31%) opposite the abasic site. The UmuC104 mutant protein was defective both in lesion bypass and in DNA synthesis. These results indicate that UmuC is a UmuD'-, RecA-, and SSB-activated DNA polymerase, which is specialized for lesion bypass. UmuC is a member of a new family of DNA polymerases which are specialized for lesion bypass, and include the yeast RAD30 and the human XP-V genes, encoding DNA polymerase eta.